E-journal and E-proceeding environment: Practical development guides - Shiratuddin, Norshuhada; Wan Ishak, Wan Hussain; Hassan, Shahizan (2005)
Journal and proceedings have become an important information source in contributing to the research outcomes, knowledge development and the latest technology finding. The main functions of scholarly journals are dissemination of information, assurance of quality standards, preservation of the archive, and recognition of authors. Printed journals and proceedings have been around for years. Some most popular and highly demanded are those published by publishers such as Pergamon, Elsevier Science, IEEE, AACE and ACM. With the advancement of computer and communication technology, a new term relating to journal has been introduced and this is discussed in the next section.